การนำเสนอเนื้อหาการทำประชาพิจารณ์ของหนังสือพิมพ์รายวัน - วงศ์สุภัทร์ คงสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Six daily newspapers are selected as population for the study. This includes, Thai Rath, Daily News, Khao Sod, Mati Chon, Krungthep Thurakit, and Thai Post, that are published between 1 January to 31 December 2000, and contain content about public hearings. This resulted in a total of 426 sampled issues. Apart from doing a quantitative analysis of the content about public hearings in these sampled issues, the researcher also carried out in-depth interviews with editors, news chiefs, and reporters in order to arrive at the findings. Data analysis is in the form of descriptive statistics with percentages of frequency in reporting. The research finds that Krungthep Thurakit presented the highest amount of content about public hearings on ongoing public projects in the selected timeframe while Mati Chon presented the highest amount of general content on public hearings that have been organized. The most prevalent form of content presentation about public hearings across the six newspapers is news. The most widely used approach in the presentation of such content is giving general information, followed by projection of some ideas, presentation of debates from all sides concerned, and informing about the results of the hearings, in that respective order. As a result of hypothesis testing, this study finds that 1) all sampled daily newspapers reported about public hearings with different frequency and forms; 2) each sampled newspaper has a different approach in presenting content about public hearings; 3) each sampled newspaper has a different objective and perspective in presenting content about public hearings.